The Economic Effects of Refugee Return and Policy Implications - Dadush, Uri (World Bank, Washington, DC, 2018)
The recent surge in the number of forcibly displaced who cross international borders in search of protection has prompted interest in evaluating policies that achieve the possible "end points" of the phenomenon. As envisaged by United Nations High Commissioner for Refugees (UNHCR), these are the integration in the country of destination, relocation in a third country, and return to the country of origin. The focus of this paper is on the third aspect, namely the appropriate conduct of return policy viewed from the perspective of the host country. More specifically, the main question is whether it is in the economic self-interest of host countries to return forcibly displaced persons. In addressing the question, four ancillary issues are to be addressed: (i) the macroeconomic impact of refugees and of their return; (ii) the labor market impact of refugees and of their return, (iii) the fiscal impact of refugees and of their return; and (iv) how return policy should be formulated and executed. The available evidence and analyses allow this paper's main conclusion, namely that the costs of hosting asylum seekers and refugees are front-loaded, while the benefits accruing from their integration into the labor market and the host economy typically take years to materialize. It follows that from the economic perspective their return after a short stay may represent a costlier option than continuing to invest in their successful integration. Countries with a flexible labor market, strong investment climate, and a welcoming attitude to immigrants tend to see the economic benefits of refugee inflows materialize faster.